Cosmopolitan Archaeologies - Meskell, Lynn (Book collections on Project MUSE., 2009)
Collection of essays that consider archaeology as a global project that must attend to the cultural, political, and historical specificity of archaeological sites, while also taking into account transnational questions of human rights and heritage preserv.